The prevalence of reasons for tooth extraction in cats - Kim, Chun-Geun; Kwon, Daehyun; Lee, Kyuyoung; Kim, Se Eun; Jo, Hyun Min (Frontiers in Veterinary Science, 2025)
ObjectivesThis study aimed to determine the prevalence of diseases leading to tooth extraction in a large population of cats and to identify factors associated with each condition, including age, sex, breed, and tooth position.MethodsAll cats underwent a thorough dental examination and full mouth dental radiographs to assess their oral health. Each tooth was classified according to its primary pathological condition, and extraction was performed based on clinical criteria specific to each disease. Tooth extractions were then performed using appropriate methods based on the condition of each tooth. For a detailed analysis of each disease, a comparative study was conducted considering factors such as sex, age, breed, and tooth position.ResultsPeriodontitis (33.41%), feline chronic gingivostomatitis (FCGS, 32.40%), and tooth resorption (TR, 15.21%) were the three most frequent reasons for tooth extraction in cats. Periodontitis and TR tended to significantly increase in prevalence with age, while FCGS showed a decreasing trend with age. Periodontitis was most commonly observed in the maxillary first molar teeth and mandibular incisor teeth, and least frequently in the canine teeth, with no statistically significant differences by sex or breed. FCGS showed a higher prevalence in domestic shorthair cats, and a slightly higher extraction rate in intact females compared to spayed females. There were no statistically significant differences by tooth location. TR was most frequently found in the mandibular third premolar teeth, with no significant variation by sex. While some breeds showed higher TR prevalence, the distribution varied across breeds.Conclusions and relevanceThis study underscores the importance of tailored dental care for cats, especially as they age, and highlights the need for further studies to explore the links between factors such as nutrition, genetics, and oral health. A better understanding of these aspects can lead to improved overall health and quality of life for cats.